Simulated microgravity-cultured mesenchymal stem cells improve recovery following spinal cord ischemia in rats - Tomoyuki Kurose; Shinya Takahashi; Takashi Otsuka; Kei Nakagawa; Takeshi Imura; Taijiro Sueda; Louis Yuge (Stem Cell Research, 2019)
Spinal cord ischemia is a potential complication of thoracoabdominal aortic surgery that may induce irreversible motor disability. We investigated the therapeutic efficacy of simulated microgravity-cultured mesenchymal stem cell (MSC) injection following spinal cord ischemia−reperfusion injury. Sprague-Dawley rats were divided into sham, phosphate-buffered saline (PBS), normal gravity-cultured MSC (MSC-1 G), and simulated microgravity-cultured MSC (MSC-MG) groups. Spinal cord ischemia was induced by transient balloon occlusion of the thoracic aorta, which was followed immediately by PBS or MSC injection into the left carotid artery. Hindlimb motor function was evaluated by the Basso-Beattie-Bresnahan (BBB) scale. Spinal cords were removed 1, 3, or 7 days post-injury for immunohistochemical staining and Western blot analysis. One day post-injury, a few infiltrating inflammatory cells and small vacuoles were observed without significant group differences, followed over several days by progressive spinal cord degeneration. Glial fibrillary acidic protein (GFAP)-positive (reactive) astrocyte numbers were increased in all three groups, and brain-derived neurotrophic factor (BDNF) was colocalized with GFAP-positive cells in spinal ventral horn. Animals in the MSC-MG group demonstrated greater BDNF-positive astrocyte numbers, reduced caspase-3-positive cell numbers, and superior motor recovery. Microgravity-cultured MSC-based therapy may improve functional recovery following spinal ischemia−reperfusion injury by promoting astrocytic BDNF release, thereby preventing apoptosis. Keywords: Microgravity, Spinal cord, Ischemia−reperfusion injury, Motor function, Astrocyte, Brain-derived neurotrophic factor, Apoptosis